2017
DOI: 10.1002/cjce.23063
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a draft tube on industrial‐scale Fluid Coker™ Spray Jets in fluidized beds

Abstract: In fluidized bed reactors such as Fluid Cokers TM , liquid injections are used. Good contact between liquid and bed solids is required to maximize product yields and quality, and gas-atomized nozzles are, therefore, used in all these processes. The spray nozzle technology is known to affect the liquid distribution. Therefore, the objective of this study is to assess the effect on liquid distribution of a draft tube located downstream of the spray nozzle, inside the fluidized bed. Experiments were conducted at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Enhancing radial mixing can therefore promote interactions between droplets and particles . This can be achieved by confining the jet with a draft tube located downstream of the spray nozzle tip. , The distance from the nozzle tip should be such as to allow for sufficient particle entrainment into the jet cavity. ,, The entrainment of particles into the jet can also be improved by modifying the draft tube geometry . Although a draft tube will reduce particle entrainment into the jet, therefore increasing the average liquid content of the wet solids formed at the tip of the jet, its beneficial impact results from the reduction of variations in liquid content within the wet solids; CFD modeling confirmed that a draft tube reduces the amount of the wettest agglomerates, which are the most resistant to breakup in the fluidized bed. , Draft tubes have also been shown to improve the liquid distribution with vertical spray jets…”
Section: Reactormentioning
confidence: 99%
“…Enhancing radial mixing can therefore promote interactions between droplets and particles . This can be achieved by confining the jet with a draft tube located downstream of the spray nozzle tip. , The distance from the nozzle tip should be such as to allow for sufficient particle entrainment into the jet cavity. ,, The entrainment of particles into the jet can also be improved by modifying the draft tube geometry . Although a draft tube will reduce particle entrainment into the jet, therefore increasing the average liquid content of the wet solids formed at the tip of the jet, its beneficial impact results from the reduction of variations in liquid content within the wet solids; CFD modeling confirmed that a draft tube reduces the amount of the wettest agglomerates, which are the most resistant to breakup in the fluidized bed. , Draft tubes have also been shown to improve the liquid distribution with vertical spray jets…”
Section: Reactormentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34] Agglomeration also occurs, even with spray nozzles that generate tiny droplets, when the bed solids on which the droplets impact are not renewed fast enough; agglomerate formation can be reduced by increasing the fluidization velocity, redirecting gas bubbles to the spray jet cavity, [35] or changing the particle mixing in the spray region. [36][37][38][39][40] Laboratory experiments suggest that the benefits of a better nozzle design and better local bed hydrodynamics complement each other. [41] Finally, agglomeration is more likely to occur when the sprayed liquid wets particles more effectively, that is, when wettability is increased.…”
mentioning
confidence: 99%